Flow resistance and hydraulic geometry in contrasting reaches of a bedrock channel. Issue 3 (22nd March 2017) - Ferguson, R. I.; Sharma, B. P.; Hardy, R. J.; Hodge, R. A.; Warburton, J.
Abstract: Assumptions about flow resistance in bedrock channels have to be made for mechanistic modeling of river incision, paleoflood estimation, flood routing, and river engineering. Field data on bedrock flow resistance are very limited and calculations generally use standard alluvial‐river assumptions such as a fixed value of Manning's n . To help inform future work, we measured how depth, velocity, and flow resistance vary with discharge in four short reaches of a small bedrock channel, one with an entirely rock bed and the others with 20–70% sediment cover, and in the alluvial channel immediately upstream. As discharge and submergence increase in each of the partly or fully alluvial reaches there is a rapid increase in velocity and a strong decline in both n and the Darcy‐Weisbach friction factor f . The bare‐rock reach follows a similar trend from low to medium discharge but has increasing resistance at higher discharges because of the macroroughness of its rock walls. Flow resistance at a given discharge differs considerably between reaches and is highest where the partial sediment cover is coarsest and most extensive. Apart from the effect of rough rock walls, the flow resistance trends are qualitatively consistent with logarithmic and variable‐power equations and with nondimensional hydraulic geometry, but quantitative agreement using sediment D 84 as the roughness height is imperfect. Key Points: n and f coefficients in fully bedrock, partial‐cover and fully alluvial reaches all vary greatly with discharge but differ between reaches Flow resistance of partly covered bedrock decreases with discharge and submergence in a similar way to coarse‐bed alluvial channels Resistance in the sediment‐free bedrock reach increases at high discharges because rock walls are rougher than bed